PENGUKURAN KEPUASAN PENGGUNA E-LEARNING MENGGUNAKAN METODE EVALUASI HEURISTIK DAN SYSTEM USABILITY SCALE - ., Setiyono; Hasibuan, Muhammad Said (Jurnal informasi dan komputer, 2023)
The COVID-19 pandemic that occurred n 2020 has changed all factors of human life n socializing, working, and education. Various prevention efforts have been made by mankind to minimize the spread of the Corona virus n society, one of which s working from home, or what s known as Work From Home (WHO). All areas of education are closed, and teaching and learning activities are carried out from home. the learning process from home, one of which utilizes electric learning (e-learning). The media components used are based on video, mages, audio, digital, schoolology, and so on. So that e-learning can be used effectively and efficiently for users, two methods are used, namely heuristic evaluation and the System Usability Scale (SUS). The purpose of this test s to determine how useful the website's user nterface and contents are to users. The results of the SUS test show that the score obtained s 56.2, which places the website n the "ok" category. While the test results using the heuristic evaluation method obtained the lowest score n H1 and H2, with values of 1,214 and 1,329, respectively, they ndicate that this tem does not need significant mprovement. while the highest scores are n H3 to H10 because the resulting severity values are two types of minor problems, meaning that t needs some mprovement n each category